THE SOCIAL-PHILOSOPHICAL ESSENCE OF MILITARY SERVICE AND ITS ROLE IN THE SPIRITUAL STABILITY OF SOCIETY - Muminov Fazliddin Qobil oglu (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines the socio-philosophical essence of military service and its role in ensuring the spiritual stability of society. The study analyzes the ontological and axiological aspects of military service, highlighting its importance in transforming individuals from personal existence to social responsibility. It also explores the relationship between military service and concepts such as duty, patriotism, and moral consciousness. Furthermore, the role of military service in shaping ideological immunity in the context of modern information challenges is substantiated.